PERANCANGAN SISTEM INFORMASI AKUNTANSI PENGGAJIAN BERBASIS VISUAL BASIC 6.0 PADA PT FEBERCO PALEMBANG - Mubarok, Muhammad Husni; Dwitayanti, Yevi; Pratama, Ramod Yudha (Jurnal Pengabdian Masyarakat Akuntansi, Bisnis & Ekonomi, 2023)
PT Feberco is a construction company in Palembang City, South Sumatra Province. In payroll operational activities, the company still performs calculations manually. This community service activity utilizes Visual Basic 6.0. to design a payroll accounting information system. Interviews were carried out by the author to find out all the information and problems that occurred in the company. This community service activity will produce a computerized payroll accounting information system, which will assist the finance department in compiling one of the elements of financial reports, namely the payroll report. Keywords: Payroll, Visual Basic 6.0, Accounting Information System